Investigating the viability of rural housing finance as a vehicle for the creation of sustainable human settlement in Moletlane village – Lepelle Nkumpi municipality - Mthethwa, Zamukuhle William (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPA)--Stellenbosch University, 2014.